Epidemiology and Surveillance of Influenza Viruses in Uganda between 2008 and 2014 - Wabwire-Mangen, Fred; Mimbe, Derrick E.; Erima, Bernard; Mworozi, Edison A.; Millard, Monica; Kibuuka, Hannah; Lukwago, Luswa; Bwogi, Josephine; Kiconco, Jocelyn; Tugume, Titus; Mulei, Sophia; Ikomera, Christine; et al. (PLoS ONE, 2016)
Influenza surveillance was conducted in Uganda from October 2008 to December 2014 to identify and understand the epidemiology of circulating influenza strains in out-patient clinic attendees with influenza-like illness and inform control strategies. Methodology Surveillance was conducted at five hospital-based sentinel sites. Nasopharyngeal and/or oropharyngeal samples, epidemiological and clinical data were collected from enrolled patients. Real-time reverse transcription polymerase chain reaction (RT-PCR) was performed to identify and subtype influenza strains. Data were double-entered into an Epi Info 3.5.3 database and exported to STATA 13.0 software for analysis. Results Of the 6,628 patient samples tested, influenza virus infection was detected in 10.4% (n = 687/ 6,628) of the specimens. Several trends were observed: influenza circulates throughout the year with two peaks; the major one from September to November and a minor one from March to June. The predominant strains of influenza varied over the years: Seasonal Influenza A(H3) virus was predominant from 2008 to 2009 and from 2012 to 2014; Influenza A (H1N1)pdm01 was dominant in 2010; and Influenza B virus was dominant in 2011. The peaks generally coincided with times of higher humidity, lower temperature, and higher rainfall. Conclusion Influenza circulated throughout the year in Uganda with two major peaks of outbreaks with similar strains circulating elsewhere in the region. Data on the circulating strains of influenza and its patterns of occurrence provided critical insights to informing the design and timing of influenza vaccines for influenza prevention in tropical regions of sub-Saharan Africa.
Keywords: Epidemiology; Surveillance; Influenza Viruses; Uganda